Surgery Outcomes of Glaucoma Drainage Device Implantation in Refractory Glaucoma Patients at Sardjito General Hospital: Oral Presentation - Observational Study - Resident - Saputra, Yuandani; Jati, Krisna Dwi Purnomo; Ekantini, Retno; Gani, Tatang T (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesGlaucoma drainage device (GDD) implantation was an effective surgical procedure in treatinguncontrolled intraocular pressure (IOP) of glaucoma patients in certain complicated conditions. GDDimplants were classified into valved and non-valved in which its surgical outcomes in different typesof device and various etiologies were not similar. This study aimed to evaluate the surgery outcomesof GDD implantation in patients with refractory glaucoma at Sardjito General Hospital. MethodsAll 12 eyes of 11 patient’s medical records who underwent GDD implantation during 2022 at SardjitoGeneral Hospital was reviewed. Baseline data include age, gender, eye laterality, type of glaucoma,IOP and visual acuity. The IOP and visual acuity (LogMAR) were measured at week 1, month 1, 2and 3. Type of GDD implants, postoperative glaucoma medications, complications and need forfurther glaucoma surgery were documented. ResultsThe mean IOP at baseline was 44 ± 14.2 mmHg with 3.4 ± 0.6 glaucoma medications. It decreasedafter surgery into 19.1 ± 11.2 mmHg (p=0.003) at 3 months follow up with 0.7 ± 1.7 (p=0.002)glaucoma medications. The mean initial visual acuity was 1.9 ± 0.6 and changed insignificantly to1.7 ± 0.8 (p=0.624) at last follow up. Six eyes (50%) were implanted with valved implant. The mostcommon early postoperative complications were recurrent high IOP (4 eyes, 33.3%) associated toripcord of non-valved implant (p=0.025). Five eyes (41.7%) needed additional surgery related tonon-valved implant type (p=0.003). ConclusionGDD implantation especially valved type appears to be safe and effective surgical option in treatingrefractory glaucoma patients.